2020
DOI: 10.3390/ma13143184
|View full text |Cite
|
Sign up to set email alerts
|

Field-Assisted Sintering/Spark Plasma Sintering of Gadolinium-Doped Ceria with Controlled Re-Oxidation for Crack Prevention

Abstract: Gadolinium-Doped Ceria (GDC) is a prospective material for application in electrochemical devices. Free sintering in air of GDC powder usually requires temperatures in the range of 1400 to 1600 °C and dwell time of several hours. Recently, it was demonstrated that sintering temperature can be significantly decreased, when sintering was performed in reducing atmosphere. Following re-oxidation at elevated temperatures was found to be a helpful measure to avoid sample failure. Sintering temperature and dwell time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Similar behavior was observed in the case of the higher electrical field experiments on ceria 24 and GDC 7 . Generally, enhanced grain growth of GDC is observed throughout the sample when conventionally free sintered under reducing atmosphere 2,60 . Due to the presence of an electrical field across the sample, the oxygen vacancies are expected to accumulate at the negative electrode side, and courser grains are expected there.…”
Section: Discussionsupporting
confidence: 71%
“…Similar behavior was observed in the case of the higher electrical field experiments on ceria 24 and GDC 7 . Generally, enhanced grain growth of GDC is observed throughout the sample when conventionally free sintered under reducing atmosphere 2,60 . Due to the presence of an electrical field across the sample, the oxygen vacancies are expected to accumulate at the negative electrode side, and courser grains are expected there.…”
Section: Discussionsupporting
confidence: 71%
“…All rights reserved powder is difficult handle with respect to agglomeration and may not be cost effective for large scale production. The sintering aids may deteriorate the electrochemical properties 26 , and using reducing atmosphere requires re-oxidation at a high temperature to reliably avoid the microcracking 25,27 .…”
Section: Accepted Articlementioning
confidence: 99%
“…It has been observed that the loss of oxygen is most severe at the interface in direct contact with the electrodes. On a macroscopic scale, samples fracture into several pieces during ejection from the die.Inhomogeneous chemical expansion, induced by non-uniform reduction of the sample leads to internal stresses causing this phenomenon 27,36 . The chemical expansion of GDC is related to the volume expansion and contraction with oxygen depletion and accumulation in the lattice respectively 27 .…”
Section: Accepted Articlementioning
confidence: 99%
“…When cerium dioxide is consolidated by FS or SPS, asymmetric structures are readily created, possibly resulting from electrochemical reduction; such behavior was reviewed in our previous work 15 . The ability of cerium to change its oxidation state (IV to III) and the creation of oxygen sub‐stoichiometric phases enhanced by the passing current lead to the structural asymmetry and later to disintegration of the compacts 16 . Several authors have described the compaction of pure or lanthanide‐doped CeO 2 by SPS 17‐20 or high‐pressure SPS 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…15 The ability of cerium to change its oxidation state (IV to III) and the creation of oxygen sub-stoichiometric phases enhanced by the passing current lead to the structural asymmetry and later to disintegration of the compacts. 16 Several authors have described the compaction of pure or lanthanide-doped CeO 2 by SPS [17][18][19][20] or high-pressure SPS. 21,22 Mostly, these results showed a conventional sintering behavior typical for oxide refractory ceramics.…”
mentioning
confidence: 99%